PENGARUSUTAMAAN MANAJEMEN TALENTA DALAM TATA KELOLA MSDM BIROKRASI INDONESIA - Adima Insan Akbar Noors (Institut Pemerintahan Dalam Negeri, 2019)
This paper tries to explain the importance of Talent Management in bureaucratic governance in Indonesia. The Indonesian government currently only focuses on conducting open selection and in fact it raises several problems. The research method used in this paper is descriptive qualitative. In this writing, the author uses Talent Management theory as a regulatory analysis tool in Indonesia